Multiple breath washout in bronchiectasis clinical trials: is it feasible?. Issue 4 (13th October 2020) - O'Neill, Katherine; Ferguson, Kathryn; Cosgrove, Denis; Tunney, Michael M.; De Soyza, Anthony; Carroll, Mary; Chalmers, James D.; Gatheral, Timothy; Hill, Adam T.; Hurst, John R.; Johnson, Christopher; Loebinger, Michael R.; et al.
Background: Evaluation of multiple breath washout (MBW) set-up including staff training, certification and central "over-reading" for data quality control is essential to determine the feasibility of MBW in future bronchiectasis studies. Aims: To assess the outcomes of a MBW training, certification and central over-reading programme. Methods: MBW training and certification was conducted in European sites collecting lung clearance index (LCI) data in the BronchUK Clinimetrics and/or i-BEST-1 studies. The blended training programme included the use of an eLearning tool and a 1-day face-to-face session. Sites submitted MBW data to trained central over-readers who determined validity and quality. Results: Thirteen training days were delivered to 56 participants from 22 sites. Of 22 sites, 18 (82%) were MBW naïve. Participant knowledge and confidence increased significantly (p<0.001). By the end of the study recruitment, 15 of 22 sites (68%) had completed certification with a mean (range) time since training of 6.2 (3–14) months. In the BronchUK Clinimetrics study, 468 of 589 (79%) tests met the quality criteria following central over-reading, compared with 137 of 236 (58%) tests in the i-BEST-1 study. Conclusions: LCI is feasible in a bronchiectasis multicentre clinical trial setting; however, consideration of site experience in terms of training as well as assessment of skill drift and the need for re-training may be important to reduce time to certification and optimise data quality. Longer times to certification, a higher percentage of naïve sites and patients with worse lung function may have contributed to the lower success rate in the i-BEST-1 study. LCI is feasible in a bronchiectasis multicentre clinical trial setting; however, consideration of site experience in terms of training as well as assessment of skill drift and the need for re-training may be important to optimise data quality https://bit.ly/2WZ4L1e